1973
DOI: 10.1098/rspb.1973.0034
|View full text |Cite
|
Sign up to set email alerts
|

The growth of tumours in T-cell deprived mice and their response to treatment withCorynebacterium parvum

Abstract: Severe depletion of thymus-derived lymphocytes does not reduce, and may significantly increase, the resistance of mice to syngeneic tumours, although it grossly impairs their ability to reject allotransplants. Injection of killed C. parvum causes further inhibition of tumour growth in T-cell deprived mice to an extent comparable to that resulting from the same dose of C.parvum in normal mice. This appears to lend support to the hypothesis that the antitumour effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
1

Year Published

1974
1974
1982
1982

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 3 publications
2
21
1
Order By: Relevance
“…However, as C. parvum is a known immunopotentiating agent (Halpern et al, 1963;Howard, Scott and Christie, 1973), most emphasis has been on the role played by macrophages and T cells (Woodruff, Dunbar and Ghaffar, 1973;Olivotto and Bomford, 1974). In this paper we present evidence of a non-immunological action of C. parrum which could possibly inhibit tumours, particularly metastases, in the liver and lungs.…”
mentioning
confidence: 59%
“…However, as C. parvum is a known immunopotentiating agent (Halpern et al, 1963;Howard, Scott and Christie, 1973), most emphasis has been on the role played by macrophages and T cells (Woodruff, Dunbar and Ghaffar, 1973;Olivotto and Bomford, 1974). In this paper we present evidence of a non-immunological action of C. parrum which could possibly inhibit tumours, particularly metastases, in the liver and lungs.…”
mentioning
confidence: 59%
“…Mice.-The recipient mice were either intact adult CBA females (20-22 g) or T-cell deprived CBA females prepared as described previously (Woodruff et al, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…We have used as tumour hosts both intact and T-cell deprived mice, because in our own experience (Wooodruff and Dunbar, 1972;Woodruff, Dunbar and Ghaffar, 1973), the anti-tumour effect of systemic injections of active strains of C. parvum in respect of cholanthrene induced sarcomata is maintained in T-cell deficient mice, whereas Scott (1974) has reported that the growth of a mastocytoma, is inhibited by intratumour injection of C. parvum in intact mice but not in T-cell deprived mice.…”
mentioning
confidence: 99%
“…The present experiments also establish that the increase in certain Ig levels (and possibly anti-tumourresponses) following C. parvum administration are to some extent independent of T-cell function. These serological observations are important in relation to the known antitumour properties of systemically administered C. parvum in T-deprived and nude mice (Woodruff et al, 1973;Woodruff and Warner, 1977).…”
mentioning
confidence: 99%